Income and price elasticities of demand in South Africa: An application of the linear expenditure system - Rulof Burger; Wicus Coetzee; Friedrich Kreuser; Neil Rankin (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
This paper investigates the expenditure patterns of South African households using detailed cross-sectional expenditure and price data. Linear expenditure system (LES) parameter estimates are used to calculate income and price elasticities for a number of product categories at different points of the income distribution. We find substantial variation in the price and income elasticity of demand of items across the income distribution, with the bottom quartile being extremely sensitive to increases in the price of food and clothing items, and the top quartile being as sensitive as households in developed countries.
Keywords: D12; D31; 330; demand elasticity; household food demand; income and price elasticity; linear expenditure system